PENGARUH PENGGUNAAN METODE BERCERITA TERHADAP PRESTASI BELAJAR SISWA DALAM MATA PELAJARAN PAI (Penelitian di Kelas V SDN 1 Bayasari Kecamatan Jatinagara Kabupaten Ciamis) - Herlina, Elin; Azis, Abdul; Munandar, Didih Syakir (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2015)
This study aims to analyze the effect of using storytelling methods on student learning achievement in PAI subjects. Based on the results of data collection and data processing can be concluded: 1) The use of the method of telling stories in Class V SDN 1 Bayasari, Jatinagara District, Ciamis Regency, was in the high category. This result is evidenced by the average value obtained from the questionnaire that has been distributed to respondents at 89.21, because it is in the range of 80-100, it is categorized as very high / good. 2) Student learning achievement in Class V SDN 1 Bayasari Jatinagara District, Ciamis Regency in the PAI subject is 82.93, because it is in the range of 80 - 100, the student achievement in PAI subjects is in the good / high category. 3) The effect of using storytelling methods on student achievement in PAI subjects in Class V SDN 1 Bayasari, Jatinagara District, Ciamis District has a very significant effect. This is evidenced from the results of the research obtained by the correlation coefficient number (r) of 0.496, which means the significance of 0.05 confidence level. Angaka 0.496 is in the interval from 0.40 to 0.70, which means the level of correlation is moderate. And after being tested with the formula t, the correlation coefficient of 0.496 produces the magnitude of the effect of the variable X on Y by 13%. While the degree of absence of influence is 87%, so it can be interpreted that each increase in variable X will affect Y variable by 13%, while 87% is influenced by other factors.